Development of a Virtual Laboratory for Bacterial Culture as a Biology Learning Media - Lopiani, Salmanera Senja; Muzakki, Muhammad Naufal; Fahmi, Wahyunisa Maulia; Wardhani, Irma Yuniar; Fikri, Achmad Ali (Universitas Islam Negeri Ar-Raniry, 2025)
This research aims to develop a virtual laboratory Android application entitled